A Structured Approach to Understanding the Financial Service Needs of the Poor in Mexico - Faz, Xavier; Breloff, Paul (2012)
Financial service providers have traditionally focused more on the supply side of financial inclusion than on the demand side. Undoubtedly, it is easier to measure number of branches; total customers served, and aggregated portfolios rather than attempt to get into the messy business of poor and underserved customers' lives, businesses, and needs. However, authors are starting to recognize the fundamental importance of working directly with customers to understand their financial habits and needs, as well as the role of finance in their lives. This brings a new perspective on the problem of financial inclusion: a deeper understanding of demand could be key to designing a more meaningful and sustainable offering, particularly as authors realize how little we actually know. The study also helped us understand the value of informal options used today. Saving at home is easy, low cost, and convenient. Informal credit is easily accessible from family and friends, bears little or no interest, and has flexible terms of repayment.